The Combined Effect of Indoor Air Quality and Socioeconomic Factors on Health in Northeast China - Yu Chen; Bin Chen (Applied Sciences, 2020)
Research has increasingly demonstrated that complex relationships exist between residential indoor air quality, health and socioeconomic factors. However, few studies have provided a comprehensive understanding of these relationships. The purpose of this paper, therefore, was to use structural equation modeling to identify the combined effect of residential indoor air quality and socioeconomic factors on occupants’ health, based on field measurement data in Northeast China. The results showed that socioeconomic status had a direct impact on the occupants’ health with the path coefficient of 0.413, whereas the effect from indoor air quality was 0.105. Socioeconomic status posed the direct effect on indoor air quality with path coefficients of 0.381. The weights of PM2.5, CO2, TVOC (Total Volatile Organic Compounds), and formaldehyde concentration to the indoor air quality were 0.813, 0.385, 0.218, and 0.142, respectively. Relative contributions of Income level, education level, and occupation prestige to socioeconomic status were 0.595, 0.551, and 0.508, respectively. Relationships between indoor air quality, socioeconomic factors and health were further confirmed based on multiple group analysis. The study defines and quantifies complex relationships between residential indoor air quality, socioeconomic status and health, which will help improve knowledge of the impacts of the residential indoor environment on health.